Collective properties of physical systems : proceedings of the twenty-fourth Nobel Symposium held June 12-16, 1973 at Aspenasgarden, Lerum, Sweden. - Lundqvist, B. I. (Bengt I.); Lundqvist, Stig, 1925-; Runnstrom-Reio, Vera, 1919- (Medicine and natural sciences., 1973)
References; Key words; Discussion; Chapter 11. The Order Parameter in Liquid 3He; References; Discussion; Chapter 12. Aligned Orbital Angular Momentum in the Low Temperature Phase of 3He; References; Discussion; Chapter 13. NMR in an Anisotropie Superfluid (3He); References; Discussion; Chapter 14. Remarks on Anisotropic Superfluids; References; Chapter 15. Spin Fluctuations and Anisotropic Superfluidity in 3He; Summary; I. Summary of Spin Fluctuation Calculation; II. Inclusion of Particle-Particle Scattering; III. Numerical Comparison with He; References; Discussion